The Roman war of Antiochos the Great - Grainger, John D., 1939- (Mnemosyne, Supplements, 2002)
This is the first detailed study of the collision of the two greatest powers of the Hellenistic world. The Roman Republic, victorious over Carthage and Macedon, met the Seleukid kingdom, which had crushed Ptolemaic Egypt. The preliminary diplomatic sparring was complicated by Rome's attempts to control Greece, and by the military activities of Antiocohos the Great, and ended in war. Despite well-meaning attempts on both sides to avoid and solve disputes, areas of disagreement could not be removed. Each great power was hounded by the ambitions of its subsidiary clients. When the Aitolian League deliberately challenged Rome, and Rome seemed not to respond, Antiochos moved into Greece to take Rome's place. The Roman reaction produced the war, and a complex campaign by land and sea resulted in another Roman victory.